A randomized clinical trial of a new perioperative practice model on anxiety and health-related quality of life in arthroplasty patients - Pulkkinen Maria; Jousela Irma; Sintonen Harri; Engblom Janne; Salanterä Sanna; Junttila Kristiina (WILEY, 2022)
Aims: To explore the effectiveness of a new perioperative practice model on anxiety and health-related quality of life in patients undergoing total hip arthroplasty and total knee arthroplasty under spinal anaesthesia.
Design: A randomized clinical trial.
Methods: Control group participants (N = 222) received standard perioperative care, meaning they were cared for by various nurses during their perioperative process without postoperative visits. Intervention group participants (N = 231) were assigned one named anaesthesia nurse during their entire perioperative process who visited them postoperatively. Both groups responded to two self-reported questionnaires: the generic 15D health-related quality of life instrument and the State-Trait Anxiety Inventory (STAI) measuring anxiety two to three weeks pre-operatively and three months postoperatively.
Results: There were no statistically significant differences between the groups at baseline or at follow-up in health-related quality of life or anxiety.